2020
DOI: 10.1136/neurintsurg-2020-016218
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of Millipede 088 intracranial aspiration catheter in cadaver and in vitro thrombectomy models

Abstract: BackgroundLarger bore aspiration catheters are expected to significantly improve the speed and completeness of acute stroke revascularization.ObjectiveTo evaluate the navigability and clot retrieval performance of a novel 8Fr aspiration catheter, Millipede 088 (Perfuze Ltd), using fresh-frozen cadavers and an in vitro thrombectomy model, respectively.MethodsCadaveric study: Transfemoral catheterization of the intracranial arteries was performed in six cadavers, allowing evaluation of navigation to 12 middle ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…A recent study using similar human clot analogs in an in vitro thrombectomy system also demonstrated that the composition of the clot analogs significantly affects the outcome of the procedure. 36 By assessing the success rate of all of the various thrombectomy devices and techniques in retrieving different phenotypes of clots as described, we can arrive at a better understanding of how to improve the rates of FPE. The use of human clot analogs and accurate in vitro thrombectomy systems could be a valuable training resource for educating physicians on the potential clinical significance of tailoring their treatment strategy to optimize their chances of achieving complete revascularization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study using similar human clot analogs in an in vitro thrombectomy system also demonstrated that the composition of the clot analogs significantly affects the outcome of the procedure. 36 By assessing the success rate of all of the various thrombectomy devices and techniques in retrieving different phenotypes of clots as described, we can arrive at a better understanding of how to improve the rates of FPE. The use of human clot analogs and accurate in vitro thrombectomy systems could be a valuable training resource for educating physicians on the potential clinical significance of tailoring their treatment strategy to optimize their chances of achieving complete revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Suction catheters that can generate a large suction force to deform the clots and overcome the clot friction to ingest the clots could be beneficial. 40 However, the thrombectomy tests are performed in a glass phantom, and the arterial response to suction was not captured. Under suction, the vessel could collapse due to the reduced intraluminal pressure and evacuation of fluid, hypothetically related to the more severe vessel injuries using suction catheters rather than the stent retrievers.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, 8F 0.088-in (I.D.) aspiration catheters (Millipede 088, Perfuze Ltd;) and (0.088 in, Route 92 Medical, Inc., San Mateo, CA) have been proven feasible to navigate in preclinical models of the M1 segment and the basilar artery and to be superior in clot extraction compared with smaller bore catheters ( 45 ). However, in this study, there is no published clinical data on safety and efficacy profiles of these catheters from use in patients.…”
Section: Devicesmentioning
confidence: 99%
“…Recently, the limits of large bore aspiration have been pushed even further, as early experiences have been published reporting the safe use of 0.088" lumen aspiration catheters to perform MCA thrombectomies (Figure 4) (65). Other 0.088" aspiration catheters are currently undergoing benchtop testing (66), and more exotic designs (such as the R4Q, MIVI Neuroscience, Inc., Eden Prairie, MN) have been offered to increase function lumen size without increasing the outer catheter diameter (67). While it is thought that such large lumen sizes may improve recanalization rates by offering higher suction force as well as a degree of flow restriction proximal to the clot, evidence for the benefits of large bore aspiration is not unequivocal, and controlled trials will be necessary (68).…”
Section: Current Directionsmentioning
confidence: 99%